A New Social Class: From Proletariat to Precariat - Toshchenko, Zhan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article deals with the emergence of a new social class, precariat, explains the causes that brought it into being, its structure and key characteristics. It traces the maturing of the idea of precariat in scientific thought, in world and Russian social practice. The main features of this class are revealed and a comparison is made with other social groups. The article reveals the specificities of this class, its place and role in contemporary divisionof labour, its position in the labour market and the first sprouts of its self-awarenessas "a class for itself". The consequences of the existence and functioning of the precariat are discussed.
Keywords: society; social class; precariat; proletariat; labour market; employment